2012
DOI: 10.1007/s10597-012-9493-2
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of a Community-Based Telepsychiatry Program in Rural Alabama: Lessons Learned—A Brief Report

Abstract: The purpose of this paper is to describe the partnership between a community-based rural mental health clinic and an academic health center to provide telepsychiatry services in rural Alabama. The partnership was developed to meet the needs of a clinic that serves an underserved rural population with limited psychiatric services. This paper offers valuable lessons learned for mental health practitioners who may be considering the benefits and challenges of forming community-based partnerships in use of telepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…When searching the literature for other important considerations, the primary topic that surfaced was partnerships with communities when implementing effective task‐sharing programs. Partnerships when developing and implementing interventions allow for plans that are suitable to the local context and meet local needs . For example, a “soft entry” program in which community‐based substance abuse counselors offered themselves as a resource to a program led by the aboriginal communities in Australia improved the engagement of aboriginal women in treatment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When searching the literature for other important considerations, the primary topic that surfaced was partnerships with communities when implementing effective task‐sharing programs. Partnerships when developing and implementing interventions allow for plans that are suitable to the local context and meet local needs . For example, a “soft entry” program in which community‐based substance abuse counselors offered themselves as a resource to a program led by the aboriginal communities in Australia improved the engagement of aboriginal women in treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Partnerships when developing and implementing interventions allow for plans that are suitable to the local context and meet local needs. 57 For example, a "soft entry" program in which community-based substance abuse counselors offered themselves as a resource to a program led by the aboriginal communities in Australia improved the engagement of aboriginal women in treatment. 58 This partnership approach creates a shift in the power dynamic that may be particularly important for indigenous communities that have faced a history of colonization.…”
Section: Partnerships With Communitiesmentioning
confidence: 99%
“…Using new audio-video technology to remove the barriers of time and distance for individuals who are most in need of medical and health care services is not a new idea, yet it has become increasingly popular in recent years (Wilson and Maeder, 2015). In the realm of psychiatry, diagnoses and treatment decisions are frequently based on record review, patient interview, and observation, enabling telepsychiatry to quickly evolve as an alternative to office visits for patients who do not have easy access to mental health services (Deslich et al, 2013; Ulzen et al, 2013). This could be a particularly attractive option for rural patients for whom face-to-face treatment access is limited.…”
Section: Introductionmentioning
confidence: 99%
“…While one recent pilot study compared telemedicine and face-to-face testing (24) and demonstrated that these were comparable, our study looked at interactions over two testing sessions, and included within-subject comparisons. Our study also adds to the growing evidence of applicability of telemedicine-based services for psychiatric care in rural areas (25;26). …”
Section: Discussionmentioning
confidence: 62%